Management of Fibrous Dysplasia of the Mandible By Excision And Bone Grafting - I. N. Tiwari; D. Venkatratnam; K. S. Mehdiratta; K. K. Srivastava (Indian Journal of Plastic Surgery)
The occurance of fibrous dysplasia as & mopo-ostotic lesion on the mandible is comparatively rare. Authors had occasion to treat a young patient by total excision of the growth and replacement of the defect of the mandible by a bone graft.